Problematika Guru Dalam Pembelajaran Kitabah Di MTs Negeri 2 Deli Serdang - Eka Septiana; Anggun Salsabila Samosir; Annisa Salsabila; Yana Kianshi Hasugian; Sahkholid Nasution (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Writing is one of the Arabic language skills, in learning it, writing has several problems, especially for teaching staff or teachers in a school. Therefore, in this research, researchers will discuss the problems faced by teachers in learning writing at Madrasah Tsanawiyah Negeri 2 Deli Serdang. This research uses a qualitative-descriptive method, the data collection method uses interviews and observation, interviews wera conducted with 4 Arabic language subject teachers who teach at the school and observation was used to observe the teacher`s difficulties in teaching writing to students and the efforts made by the teacher. The results of the research show that the problems in this school are 1) Limited knowledge of mufradat for students, 2) Educational background at the previous level which was not based on Islam, 3) Low interest and motivation of students in learning Arabic, especially writing. To overcome all these problems, the teachers made several efforts to facilitate good learning of the book, such as providing mufradat memorization at each meeting, giving imla` assignments, assigning students to answer question and writing them on the blackboard, and often providing motivation to arouse students` enthusiasm in study.